Teachers’ Teaching Reflection: English Teachers’ Challenges in Rural Areas of Indonesia - Rahmi Fadilah; Honesty Yonanda Ayudhia; Vischa Mansyera Pratama; Violintikha Harmawan (LET: Linguistics, Literature and English Teaching Journal, 2023)
Issues about education in the urban areas and rural areas are crucial in the Indonesian context. The reason is the differentiation of the quality of the Indonesia education across the country because of those areas. During their practice, English teachers in that area face many limitations that hinder the process of teaching and learning. This case study aimed to explore two English teachers’ challenges in teaching in rural areas of Indonesia and how they overcome those challenges to maximize their role as a teacher through their teaching reflection on interview and document analysis. This is significant for giving the teachers’ views on facing the challenges in every condition of teaching English and for giving a picture to the government about the real condition of teaching English in the rural areas. The result showed that English teachers tried to deal with their own teaching condition and institution, their students, and socio-cultural conditions around them. As the solution, teachers overcome those problems by strengthening their roles as a teacher and understanding social pedagogy. However, there is still a need for English teachers to get more training related to their job in teaching English in rural areas.